The Role of Executive Functions for Motor Performance in Preschool Children as Compared to Young Adults - Stuhr, Christina; Hughes, Charmayne M. L.; Stöckel, Tino (Frontiers in Psychology, 2020)
Evidence suggests that executive and motor functions are functionally intertwined, with the interrelation between the two processes influenced by the developmental stage of the individual. This study examined executive and motor functions in preschool children (n = 41; 65-83 months), and investigated if, and how, preschoolers cognitive-motor functioning differs from that of young adults (n = 40; 18-31 years), who served as a control group reflecting the upper bound of cognitive-motor development. As expected, performance of young adults was significantly better than that of preschool children for all cognitive and motor domains tested. The results further showed differential associations among, and between, cognitive and motor functions in preschool children when compared to young adults. While similar correlations among motor variables are found in both groups, correlations among executive functions and between executive and motor variables are only found in preschool children. It thus appears that executive functions (especially working memory) contribute more to successful motor performance in preschool years than in young adulthood. The findings highlight the importance of considering the developmental stage and/or the proficiency level of the individual when examining cognitive-motor interactions or when drawing implications for childhood cognitive-motor training and interventions.